(untitled) (Research, Society and Development, 2020)
The use and incorporation of basalt powder in the soil have grown every year, and there are still no studies showing its effects on the physiological quality of soybean seeds. Thus, considering the importance of this response in the production system, the objective of the present work was to evaluate the physiological condition of soybean seeds after applying different doses of basalt powder in the soil. The experimental design used was completely randomized in a 3 × 4 factorial scheme, with three replications. The treatments consisted of three soybean cultivars, and four doses of basalt powder (0, 1, 3, and 5 t ha-1) produced in the 2018/2019 harvest in the region of Chapadão do Sul, MS. The tests carried out were: first germination count, germination, electrical conductivity, dry mass of the upper plant and roots, and tetrazolium test (vigor, viability, mechanical damage, moisture, and bed bug damage). The results were submitted to the normality test and analysis of variance, followed by comparisons of means by the Tukey test at the level of 5% probability. The results showed for the first time the combined effects of both factors tested only on the variables: electrical conductivity, root length, vigor, viability, and mechanical damage. The response obtained was dependent on the cultivars evaluated, which differed for all measured characteristics.